Risks in teaching manipulation techniques in master programmes. (September 2016) - Pool, Jan; Cagnie, Barbara; Pool-Goudzwaard, Annelies
Abstract: High Velocity Techniques (HVT) in the (high) cervical spine are part of the standard curricula of manual therapy educational programmes. Little is known about the risk or the presence of adverse events during skills training sessions. This article describes two cases of students with both being at risk for an adverse event; one with a congenital artery aberration and one with cancer in the high cervical region. Teachers and educational programme developers should take risk management into account when teaching HVT. Highlights: Little is known about the risk or the presence of adverse events during skills training. Teachers and educational program developers should take risk management into account. A risk benefit analysis and a written informed consent is recommended.